Prevalence of autism among adults in Canada: results from a simulation modelling study - Christa Orchard; Amy Farrow; Stelios Georgiades; Siobhan O’Donnell; Rojiemiahd Edjoc; Erin Collins; Christoffer Dharma; Mackenzie Salt; Kieran Holmes; Sarah Palmeter; Ahmed Al-Jaishi (BMJ Open)
Objective To estimate the prevalence of autism among adults living in Canada.Design A Monte Carlo simulation modelling approach was employed. Input parameters included adult population estimates and mortality rates; autism population all-cause mortality risk ratios; and autism prevalence estimates derived from child and youth data due to the lack of adult data. This approach was executed through 10 000 simulations, with each iteration generating a distinct data scenario. Prevalence estimates were reported as the mean with the 2.5th and 97.5th percentiles, corresponding to a 95% simulation interval (SI).Setting Where possible, Canadian data sources were used, including the 2019 Canadian Health Survey on Children and Youth and Statistics Canada mortality rates and population estimates.Primary outcome measure National prevalence estimates of autistic adults living in private dwellings in Canada, with variations in prevalence by sex at birth and province/territory considered.Results The findings suggest the prevalence of autism among adults in Canada to be 1.8% (95% SI 1.6%, 2.0%). National prevalence estimates by sex at birth were 0.7% (95% SI 0.6%, 0.9%) for females and 2.9% (95% SI 2.6%, 3.2%) for males. Provincial/territorial estimates ranged from 0.7% in Saskatchewan (95% SI 0.3%, 1.3%) to 3.6% in New Brunswick (95% SI 2.4%, 5.1%).Conclusions The limited availability of data on autistic adults constrains our ability to fully understand and address their unique needs. In this study, autism prevalence was estimated based on diagnosed cases, which excludes individuals without a formal diagnosis. Additionally, other factors such as data availability and methodological assumptions may influence the modelling of prevalence estimates. As a result, our findings should be interpreted within the context of these limitations. Nevertheless, this study provides a valuable reference point for understanding autism prevalence among adults in Canada.